Long-term health outcomes of preterm birth: a narrative review - Gette, Faith; Aziz Ali, Sumera; Ho, Matthew S. P.; Richter, Lindsay L.; Chan, Edmond S.; Yang, Connie L.; Kieran, Emily; Mammen, Cherry; Roberts, Ashley; Kang, Kristopher T.; Wong, Jonathan; Rassekh, Shahrad R.; et al. (Frontiers in Pediatrics, 2025)
Despite a significant reduction in neonatal mortality due to advances in neonatal care, preterm birth (PTB) continues to pose a challenge due to the escalating incidence of long-term complications, which refer to health issues that persist or emerge beyond the immediate neonatal period. The impact of PTB, particularly in extremely preterm infants born before 28 weeks of gestational age, is not confined to the early years but extends across the lifespan, influencing physical, cognitive, and social development, as well as long-term health outcomes. These complications, which often persist from childhood into adulthood, span multiple systems and create a broad spectrum of health concerns. This comprehensive narrative review of literature delves into the breadth of well-characterized long-term complications associated with PTB, including neurodevelopmental, respiratory, cardiovascular, renal, gastrointestinal, and endocrine system disorders. By providing health care providers with a holistic understanding of the potential complications following PTB, this review aims to summarize the current literature and underscore the value of long-term monitoring strategies and proactive evaluations of this population. Our objective is to foster a clinical approach that anticipates these complications, enabling early interventions and better management of these at-risk infants.